A super-lightweight flame-retardant rubber foam material, a preparation method and applications thereof

CN120098350BActive Publication Date: 2026-10-09TIANJIN GUOXIN RUBBER & PLASTIC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510393773.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-09
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

这种填料式改性方法使得材料的阻燃性、力学性能和发泡倍率难以同时提升,综合性能难以满足多领域的实际需求

Benefits of technology

1、本发明采用在羧基丁腈橡胶分子链上引入六羟甲基三聚氰胺的接枝改性技术方案,从分子结构上实现了本征阻燃能力的提升,避免了外加阻燃剂对发泡性能和密度的负面影响,相较于现有技术中通过大量外加阻燃剂或含卤素阻燃剂实现阻燃效果的方法,本发明有效解决了材料易燃性、环境污染以及制品密度过高的问题,为阻燃泡沫材料的轻量化与环保化提供了全新途径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120098350B_ABST
    Figure CN120098350B_ABST
Patent Text Reader

Abstract

The application relates to the field of high-performance flame-retardant materials, and discloses a super-light flame-retardant rubber foam material and a preparation method and application thereof, wherein the material comprises modified carboxyl nitrile rubber, a foaming agent, a foaming aid, a crosslinking agent, a flame retardant, an inorganic filler, an adhesion resin and a softening agent; the modified carboxyl nitrile rubber is prepared by chemically grafting hexamethylenetriazine; nitrogen-containing structures are introduced into polymer molecular chains, so that the material has intrinsic flame-retardant properties, high foaming ratios and light weight, and the problems of density increase and performance deterioration caused by high filling of flame retardants in traditional technologies are avoided; the flame-retardant performance of the material reaches UL-94 V0 level, and the material is suitable for the fields of building thermal insulation, automobile interior decoration, cable sheath and household appliance shock-absorbing pads.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-performance flame-retardant materials technology, specifically to an ultra-lightweight flame-retardant rubber foam material, its preparation method, and its application. Background Technology

[0002] In existing technologies, foam materials are widely used in building insulation, automotive interiors, cable sheathing, and appliance shock absorbers due to their lightweight, thermal insulation, and superior mechanical properties. However, since foam materials are usually composed of pure organic polymers, their flammability remains a significant factor limiting their application. To improve the flame-retardant properties of these materials, existing technologies mainly achieve flame-retardant functionality by adding flame retardants or using halogen-containing flame-retardant materials, but these solutions have significant shortcomings in practical applications.

[0003] In traditional flame retardant solutions, halogenated materials are widely used due to their high flame retardant efficiency and low dosage. However, this technology presents significant environmental and health problems. Halogenated flame retardants release toxic gases such as hydrogen chloride during combustion, posing harm to human health and the environment. Furthermore, with increasingly stringent environmental regulations, the application of halogenated flame retardant materials in construction, home appliances, and automotive interiors is facing increasing restrictions. In addition, long-term use of halogenated materials may lead to a decline in their flame retardant performance, further limiting their practical application.

[0004] To address the aforementioned issues, halogen-free flame retardants have been increasingly adopted. Adding halogen-free flame retardants such as aluminum hydroxide and ammonium polyphosphate can improve the flame retardant properties of foam materials to some extent. However, this method requires the addition of large amounts of flame retardant, typically reaching 30%-50% of the material's volume. This high proportion of flame retardant not only significantly increases the material's density but also reduces its expansion ratio, leading to uneven cell structure and decreased thermal insulation performance. Furthermore, high levels of flame retardant can compromise the material's mechanical properties, particularly compressive strength and resilience, thus affecting its service life. While halogen-free flame retardant solutions offer some environmental improvements, they have not effectively resolved the conflict between flame retardancy and lightweight design.

[0005] In the development of flame-retardant foam materials, balancing flame retardancy and expansion ratio has always been a technical challenge. In existing technologies, to improve the flame retardant performance of materials, a large amount of flame retardant is often added to the matrix material. This not only affects the expansion ratio and lightweight characteristics of the material but also adversely impacts the uniformity of the cells and the thermal insulation performance. Furthermore, due to the uneven distribution of the added flame retardant in the material, the flame retardant performance may be limited to the surface layer, preventing the formation of an effective flame-retardant structure internally, further limiting the overall performance of the material. In addition, these added flame retardants may migrate during use, leading to a decrease in flame retardant effect and thus affecting the long-term stability of the material.

[0006] Another significant shortcoming of existing technologies is the lack of methods for intrinsically optimizing the matrix material at the molecular structure level. Most flame-retardant solutions rely primarily on the addition of fillers, failing to improve the synergistic effect of flame retardancy and foaming properties of the matrix material through molecular-level modification. This filler-based modification method makes it difficult to simultaneously improve the material's flame retardancy, mechanical properties, and foaming ratio, resulting in overall performance that cannot meet the practical needs of multiple fields. Furthermore, when used in high-temperature or humid environments, traditional flame-retardant foam materials often exhibit poor thermal stability and insulation performance, further limiting their application range.

[0007] Therefore, this invention proposes an ultralight flame-retardant rubber foam material, its preparation method, and its application to overcome the shortcomings of existing technologies. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides an ultralightweight flame-retardant rubber foam material, its preparation method, and its applications. By employing a chemical grafting modification technique, nitrogen-containing hexamethylolmelamine is introduced into the carboxylated nitrile rubber molecular chain, giving the material excellent intrinsic flame-retardant properties, thus avoiding the reliance on high proportions of externally added flame retardants in traditional technologies. Simultaneously, the modified structure of the material significantly improves the foaming ratio and cell uniformity, ensuring a balance between lightweight and thermal insulation performance. Furthermore, this invention achieves a balance between flame retardancy, foaming performance, and mechanical properties through synergistic optimization of the molecular chain structure, overcoming the defect of deteriorated mechanical properties in existing technologies.

[0009] To achieve the above objectives, the present invention provides the following technical solution: an ultralight flame-retardant rubber foam material, comprising the following components by weight: Modified carboxylated butadiene-acrylonitrile rubber: 10-100 parts; Foaming agent: 10-100 parts; Foaming agent: 2-20 parts; Crosslinking agent: 1-9 parts; Flame retardant: 30-80 parts; Inorganic filler: 10-100 parts; Tackifying resin: 10-100 parts; Softener: 10-100 parts; The modified carboxylated butadiene-acrylonitrile rubber is prepared by chemical grafting modification of carboxylated butadiene-acrylonitrile rubber and hexamethylol melamine under the action of a catalyst.

[0010] Preferably, the preparation method of the modified carboxylated nitrile rubber includes the following steps: Carboxylated acrylonitrile butadiene rubber with an acid value of 25-38 mg KOH / g is dissolved in toluene solvent, with the amount of solvent being 2-5 times the mass of the rubber. After calculating the carboxyl content in the carboxylated acrylonitrile rubber, an equimolar amount of hexamethylol melamine was added, along with 0.5-5 parts of anhydrous calcium chloride as a catalyst. Stir and react for 24 hours in a water bath at 80-90℃; Toluene solvent was removed by heating and evaporation to obtain modified carboxylated butadiene-acrylonitrile rubber.

[0011] Preferably, the foaming agent is azodicarbonamide, sodium bicarbonate, or a mixture of both, with a mixing ratio of 1:1 to 3:1.

[0012] Preferably, the flame retardant is a compound of aluminum hydroxide, magnesium hydroxide and ammonium polyphosphate, in a compounding ratio of 1:1:2.

[0013] Preferably, the inorganic filler is one or more of talc, calcium carbonate, or silicon dioxide, and the particle size of the filler is 1-10 μm.

[0014] Preferably, the tackifying resin is a phenolic resin, a petroleum resin, or a C5 petroleum resin.

[0015] Preferably, a method for preparing an ultralight flame-retardant rubber foam material includes the following steps: Modified carboxylated nitrile rubber, foaming agent, foaming aid, crosslinking agent, flame retardant, inorganic filler, tackifying resin and softener are added to the internal mixer according to the formula ratio; Mix thoroughly at 80-150℃ for 5-15 minutes; The intensively mixed mixture is then molded into shape. The ultra-lightweight flame-retardant rubber foam material is prepared by foaming at 160-180℃.

[0016] Preferably, the compression molding process uses a flat vulcanizing machine, with the pressure controlled at 5-15 MPa and the time at 5-20 minutes.

[0017] Preferably, the mixing step of the modified carboxylated nitrile rubber with the foaming agent, foaming aid, crosslinking agent, and flame retardant is completed in two steps: the first step is internal mixing, and the second step is open milling. The specific steps are as follows: Intensive processing: Modified carboxylated nitrile rubber, along with some inorganic fillers, tackifying resins, and softeners, is added to an internal mixer and mixed at 80-120℃ for 5-10 minutes to obtain an initial mixture. Open-processing: Add the initial mixture, foaming agent, foaming aid, crosslinking agent, flame retardant and remaining inorganic filler into a two-roll mill and mix at 50-80°C for 5-15 minutes until the mixture is homogeneous. Molding and foaming: After the mixture is molded, it is foamed at 160-180℃ to obtain an ultra-lightweight flame-retardant rubber foam material.

[0018] Preferred applications include ultra-lightweight flame-retardant rubber foam materials in building insulation, automotive interiors, cable sheaths, or shock-absorbing pads for household appliances.

[0019] This invention provides an ultralight flame-retardant rubber foam material, its preparation method, and its applications. It possesses the following beneficial effects: 1. This invention employs a grafting modification technique that introduces hexamethylol melamine into the molecular chain of carboxylated nitrile rubber, thereby enhancing the intrinsic flame retardancy at the molecular structure level. This avoids the negative impact of added flame retardants on foaming performance and density. Compared to existing technologies that achieve flame retardancy through the addition of large amounts of external flame retardants or halogen-containing flame retardants, this invention effectively solves the problems of material flammability, environmental pollution, and excessively high product density, providing a new approach for the lightweighting and environmental protection of flame-retardant foam materials.

[0020] 2. By optimizing the ratio of foaming agent and foaming aid, and combining the uniform dispersion of modified rubber, this invention achieves the preparation of high-ratio foaming and low-density foam materials, significantly improving the lightweight characteristics of the materials. Unlike the problems of uneven cell structure and limited foaming ratio caused by excessive proportion of filler and flame retardant in the prior art, this invention overcomes the defects of high density and high material cost of traditional flame retardant materials while maintaining the foaming ratio, and meets the demand for both high performance and low cost.

[0021] 3. This invention employs a technical solution that combines a closed-cell foam structure with synergistic optimization of flame retardancy within the molecular chain. This allows the material to maintain a low thermal conductivity while possessing high-efficiency thermal insulation performance. Through the uniform distribution of the molecular-level flame-retardant network, the material exhibits excellent thermal stability in high-temperature environments. Compared with traditional flame-retardant materials, which suffer from reduced thermal insulation effect and thermal stability due to uneven foam distribution or surface migration of flame retardants, this invention effectively solves the problem of maintaining thermal insulation performance during long-term high-temperature use, significantly expanding the application value of the material in building insulation and automotive interiors.

[0022] 4. This invention combines optimized crosslinking agent ratio with uniform filler distribution, and improves the compressive strength, resilience, and fatigue resistance of the material by scientifically controlling mechanical properties and cell structure. It also exhibits excellent aging stability, and the stability of the material's performance in humid and hot environments is far superior to that of traditional unmodified rubber materials. Compared with existing foam materials that have weak mechanical properties and significant aging performance degradation, this invention solves the bottleneck problem of insufficient mechanical properties and long-term stability, providing a reliable guarantee for use in cable sheaths, shock-absorbing pads, and other high-performance applications. Attached Figure Description

[0023] Figure 1 This is a flowchart illustrating the preparation method of ultralight flame-retardant rubber foam material. Detailed Implementation

[0024] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0025] Please see the appendix Figure 1 : Example 1: Preparation of modified rubber Dissolve 100g of carboxylated nitrile rubber with an acid value of 25mgKOH / g in 400g of toluene solvent (the amount of solvent is 4 times the mass of the rubber).

[0026] Based on the carboxyl content, add an equimolar amount of hexahydroxymethyl melamine, and simultaneously add 1g of anhydrous calcium chloride as a catalyst.

[0027] The reaction was stirred for 24 hours in a water bath at 80°C.

[0028] Toluene solvent was removed by heating and evaporation to obtain hexamethylol melamine-modified carboxylated butadiene-acrylonitrile rubber.

[0029] Preparation of foamed materials formula: Modified carboxylated butadiene-acrylonitrile rubber: 100 parts; Azodicarbonamide and sodium bicarbonate (combination ratio 1:1): 50 parts; Foaming agent (zinc stearate): 5 parts; Crosslinking agent (BIPB): 5 parts; Flame retardant (aluminum hydroxide, magnesium hydroxide and ammonium polyphosphate, compounded in a ratio of 1:1:2): 60 parts; Talc powder (particle size 5μm): 20 parts; Phenolic resin: 30 parts; Paraffin oil: 30 parts.

[0030] Mixing process: Internal mixing: Modified carboxylated nitrile rubber, along with some inorganic filler (10 parts talc), phenolic resin (15 parts), and paraffin oil (15 parts), are added to an internal mixer and mixed at 100°C for 10 minutes to obtain the initial mixture. Open milling: Add the initial mixture, foaming agent, foaming aid, crosslinking agent, flame retardant and remaining inorganic filler to an open mill and mix at 70°C for 10 minutes until homogeneous.

[0031] Compression molding and foaming: The mixture is added to a flat vulcanizing machine for molding, with the pressure controlled at 10MPa and the time at 10 minutes; The molded material was foamed at 170°C for 15 minutes to obtain an ultra-lightweight flame-retardant rubber foam material.

[0032] Example 2: Preparation of modified rubber Same as in Example 1, but using carboxylated nitrile rubber with an acid value of 28 mg KOH / g and 2 g of anhydrous calcium chloride.

[0033] Preparation of foamed materials formula: Modified carboxylated butadiene-acrylonitrile rubber: 100 parts; Azodicarbonamide and sodium bicarbonate (combination ratio 2:1): 60 parts; Foaming agent: 10 parts; Crosslinking agent (DCP): 7 parts; Flame retardant (mixing ratio 1:2:2): 70 parts; Talc and calcium carbonate (mixture ratio 1:1, particle size 5μm): 30 parts; Petroleum resin: 20 parts; Paraffin oil: 40 parts.

[0034] Mixing process: Intensive mixing: Intensive mixing at 120℃ for 10 minutes; Initial processing: Refine at 60℃ for 15 minutes.

[0035] Compression molding and foaming: Same as in Example 1.

[0036] Example 3: Preparation of modified rubber Same as in Example 1, but using carboxylated nitrile rubber with an acid value of 29 mg KOH / g and 3 g of anhydrous calcium chloride.

[0037] Preparation of foamed materials formula: Modified carboxylated butadiene-acrylonitrile rubber: 100 parts; Azodicarbonamide and sodium bicarbonate (combination ratio 1:1): 70 parts; Foaming agent: 6 parts; Crosslinking agent (BIPB): 4 parts; Flame retardant (mixing ratio 1:1:2): 50 parts; Talc powder: 15 parts; Phenolic resin: 25 parts; Paraffin oil: 20 parts.

[0038] Compression molding and foaming: pressure is 8MPa, foaming time is 12 minutes.

[0039] Comparative Example 1: Preparation of modified rubber Unmodified nitrile rubber (carboxyl-free) was used. 100g of nitrile rubber was dissolved in 400g of toluene solvent. No hexamethylol melamine or anhydrous calcium chloride was added. Other operations were the same as in Example 1.

[0040] Preparation of foamed materials The formula is the same as in Example 1.

[0041] Comparative Example 2: Preparation of modified rubber The modification method is the same as in Example 1.

[0042] Preparation of foamed materials formula: Modified carboxylated butadiene-acrylonitrile rubber: 100 parts; Azodicarbonamide: 50 parts; Foaming agent: 5 parts; Crosslinking agent: 5 parts; Flame retardant (ammonium polyphosphate): 100 parts; Talc powder: 20 parts; Petroleum resin: 30 parts; Paraffin oil: 30 parts.

[0043] Test experiment: Experimental materials Example Sample: The ultra-lightweight flame-retardant rubber foam materials of Examples 1, 2, and 3 were cut to specifications according to experimental requirements.

[0044] Comparative sample: The materials used in Comparative Example 1 and Comparative Example 2 are of the same specifications.

[0045] Main equipment: Thermal conductivity meter: LaserCompFOX50; Instron 3365 Universal Mechanical Testing Machine; UL-94 Vertical Burning Tester; Constant temperature aging chamber; Laser scanning confocal microscope (for observing the microstructure of materials); Infrared thermal imager (dynamic monitoring of thermal insulation performance).

[0046] Experimental environment: temperature 25±2℃, humidity 50±5%.

[0047] Experimental steps and procedures Comprehensive Testing of Foaming Ratio, Density, and Flame Retardant Properties: Objective: To simultaneously test the material's lightweight (foaming ratio and density) and flame retardant capabilities, verifying the synergistic effect of the material's multiple properties. Experimental Methods: Expansion ratio and density: The sample was cut to 100mm×100mm×10mm. Before foaming, the length, width, and thickness were measured and the volume was calculated. After foaming, measure the sample volume and mass, and calculate the foaming ratio and density according to the formula: Expansion ratio = Volume after foaming / Volume before foaming; Density = mass / volume after foaming.

[0048] Flame retardant properties: Sample size: cut to 127mm × 12.7mm × 10mm according to the UL-94 vertical burning test; Test procedure: The sample is suspended vertically, burned for 5 seconds, and the self-extinguishing time is observed. The dripping situation is recorded. Determine the flame retardancy rating (V0, V1, or V2).

[0049] Thermal conductivity, insulation performance and thermal stability testing: Objective: To test the insulation performance and dynamic thermal stability of materials and verify their application potential in building insulation and automotive interiors.

[0050] Experimental methods: Thermal conductivity test: The sample was cut to a size of 200mm × 200mm × 20mm; The thermal conductivity was tested using a thermal conductivity meter in the range of 20-100℃ to analyze the temperature dependence of the material.

[0051] Thermal insulation performance test: Fix the sample to the thermal insulation testing device and install a thermocouple on the back; The high-temperature chamber is set to a constant temperature of 100℃. An infrared thermal imager is used to monitor the dynamic changes in the temperature of the back of the sample and record the time required for the back to heat up to 30℃.

[0052] Thermal stability test: Thermogravimetric analysis (TGA) was used to heat the samples in an air atmosphere (30-800℃, heating rate 10℃ / min) to analyze the thermal decomposition temperature and thermal stability of the materials.

[0053] Comprehensive mechanical property testing: compression performance, resilience and fatigue performance. Objective: To comprehensively evaluate the mechanical properties of the material and verify its suitability for use in shock-absorbing pads and interior trim parts.

[0054] Experimental methods: Compression performance: The sample size is 50mm × 50mm × 10mm; Test the compressive strength under 50% compression deformation on a universal testing machine and record the force-displacement curve; Rebound performance: After 100% compression release, the sample thickness resilience was measured: Rebound rate = (Thickness after compression release / Initial thickness) × 100%; Fatigue performance: After the sample was subjected to compression-release cycles (0%-50% compression deformation, frequency of 1Hz, number of cycles of 1000), the remaining thickness ratio and changes in mechanical properties were tested.

[0055] Aging resistance and microstructure testing: Objective: To verify the long-term stability and durability of the material, and to reveal the mechanism of performance change by observing the microstructure.

[0056] Experimental methods: Aging resistance test: After placing the samples in an aging chamber (70°C, 70% humidity) for 168 hours, the rate of change in density, compressive strength, and flame retardant properties was tested.

[0057] Microstructure testing: Laser scanning confocal microscopy was used to observe the morphology and distribution of pores in the material before and after aging, and to analyze the impact of aging on the microstructure of the material.

[0058] Experimental data: Table 1: Overall Performance Test Results Experimental results clearly demonstrate that the materials in the examples achieved comprehensive optimization in terms of foaming ratio, lightweighting, and flame retardant properties. Through the introduction of nitrogen into the molecular chain, the material possesses excellent intrinsic flame retardancy, achieving a UL-94V0 rating without the need for large amounts of external flame retardants. This modified structure is uniformly distributed within the matrix, improving the material's foaming performance while maintaining low density. Comparative Example 1, lacking the modified structure, suffers from severely insufficient flame retardancy and foaming ratio, while Comparative Example 2 shows improvement, but the addition of external flame retardants leads to increased density, hindering the achievement of lightweighting.

[0059] Tests on thermal insulation performance and thermal conductivity revealed the crucial role of the closed-cell structure. The high-ratio foaming of the example material created uniform closed pores, significantly reducing the continuity of the heat conduction path and resulting in superior thermal insulation compared to the comparative example. Furthermore, the example samples exhibited higher thermal decomposition temperatures in dynamic thermal stability tests, demonstrating the improvement in high-temperature resistance due to molecular chain modification.

[0060] Mechanical property tests further illustrated the advantages of the modified rubber. The material in the example not only exhibited excellent compressive strength but also demonstrated superior recovery capabilities in resilience and fatigue performance tests. Its uniformly distributed filler and optimized molecular cross-linking structure effectively disperse stress during use, extending material life. In contrast, the uneven cell distribution and filler aggregation issues of the comparative material significantly limited its applications.

[0061] Through this series of experiments, the comprehensive technical effects of this invention were verified in all aspects, from foaming and flame retardancy to heat insulation and mechanical properties. The material's multifunctionality and stability are clearly superior to existing technologies, demonstrating its broad application potential in fields such as building insulation and automotive interiors.

[0062] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A lightweight flame-retardant rubber foam material, characterized in that, Based on parts by mass, it includes the following components: Modified carboxylated butadiene-acrylonitrile rubber: 100 parts; Foaming agent: 50-70 parts; Foaming agent: 2-20 parts; Crosslinking agent: 1-9 parts; Flame retardant: 50-70 parts; Inorganic filler: 15-30 parts; Tackifying resin: 20-30 parts; Softener: 20-40 parts; The modified carboxylated butadiene-acrylonitrile rubber is prepared by chemical grafting modification of carboxylated butadiene-acrylonitrile rubber and hexamethylol melamine under the action of a catalyst; The preparation method of the modified carboxylated butadiene-acrylonitrile rubber includes the following steps: Carboxylated acrylonitrile butadiene rubber with an acid value of 25~38 mgKOH / g was dissolved in toluene solvent, with the amount of solvent being 2~5 times the mass of the rubber; After calculating the carboxyl content in the carboxylated acrylonitrile rubber, an equimolar amount of hexamethylol melamine was added, along with 0.5 to 5 parts of anhydrous calcium chloride as a catalyst. The reaction was stirred for 24 hours in a water bath at 80-90℃. Toluene solvent was removed by heating and evaporation to obtain modified carboxylated butadiene-acrylonitrile rubber; The foaming agent is a mixture of azodicarbonamide and sodium bicarbonate, with a mixing ratio of 1:1 to 2:

1. The flame retardant is a compound of aluminum hydroxide, magnesium hydroxide and ammonium polyphosphate, with a compounding ratio of 1:1:2; The inorganic filler is one or more of talc, calcium carbonate or silicon dioxide, and the particle size of the inorganic filler is 1~10μm; The tackifying resin is one of phenolic resin and petroleum resin; The preparation method of the ultralight flame-retardant rubber foam material includes the following steps: S1. Internal mixing treatment: Modified carboxylated nitrile rubber, along with some inorganic fillers, tackifying resins, and softeners, are added to an internal mixer and mixed at 80~120℃ for 5~10 minutes to obtain the initial mixture. S2. Open milling process: Add the initial mixture, foaming agent, foaming aid, crosslinking agent, flame retardant and remaining inorganic filler into an open mill and perform open milling at 50~80℃ for 5~15 minutes until the mixture is homogeneous. S3. Molding and foaming: The mixture is molded using a flat vulcanizing machine with a pressure controlled at 5~15MPa and a time of 5~20 minutes. After molding, it is foamed at 160~180℃ to obtain ultra-lightweight flame-retardant rubber foam material. The ultra-lightweight flame-retardant rubber foam material is used in building insulation, automotive interiors, cable sheaths, or shock-absorbing pads for household appliances.

Citation Information

Patent Citations

  • Oil resistance foamable end cap sealing material and preparation method thereof

    CN101649180A